Gerontology concept: Toward ego integrity through Taman Pendidikan Al-Quran (TPA) in order to second demographic bonus 2035 - AZKA KARIMA; DZIKRINA IZATUNIDA; UKHDA INDRI MARGA RISKA (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: To prepare for the demographic windfall of 2035, this study seeks to understand how Taman Pendidikan Al-Qur’an (TPA) contributes to developing strong identities among the elderly. For the elderly, TPA is a tool for achieving ego integrity. Learning to recite the Quran while upholding Islamic principles is known as TPA.Methodology: This research, which employs qualitative methods such as interviews and observations, examines the experiences of three elderly female victims of the Mount Merapi eruption in Yogyakarta, which is currently being monitored by the TPA. As a result, we can state the following as our